Citizenship Values in the Iraqi Educational Curriculum: Problems of the Curriculum and the Downsides of Application (قضايا سياسية, 2023)
The research focuses on investigating the values of citizenship in textbooks specialized in social sciences, such as: the Holy Qur’an, Arabic Language, History, Geography, National Education, and Social studies. The research goes through forty-one (41) books out of one hundred (100) books of pre-university studies, With a total of (5483) pages. The study includes three levels of education: primary, intermediate and preparatory. This study relies on the basic foundations of education for citizenship set by UNESCO. Accordingly, thirteen set of values were designed to analyze the educational programs in Iraq, the values being (justice, equality, freedom, Rights, integrity, tolerance, accountability, respect for the law, loyalty to the homeland, peace, preservation of public money, respect for others, cooperation).